Partial luteolysis during early diestrus in cattle downregulates VEGFA expression and reduces large luteal cell and corpus luteum sizes and plasma progesterone concentration - Trevisol, E. [UNESP]; Mogollón García, H. D. [UNESP]; Ackermann, C. L. [UNESP]; Lacerda, W.; Pires, R. M.L.; Laufer-Amorin, R. [UNESP]; Carvalho, R. F. [UNESP]; Franchi, F. F. [UNESP]; Castilho, A. C.S.; Rizzoto, G.; Kastelic, J. P.; Ferreira, J. C.P. [UNESP] (Elsevier, 2020)
Our objectives were to investigate potential changes in the size of steroidogenic large luteal cells (LLC) during partial luteolysis induced by a sub-dose of cloprostenol in early diestrus and to determine transcriptional variations in genes involved in corpus luteum (CL) functions. Cows were subjected to an Ovsynch protocol, with the time of the second GnRH treatment defined as Day 0 (D0). On D6, cows were randomly allocated into three treatments: Control (2 mL saline, im; n = 10), 2XPGF (two doses of 500 μg of cloprostenol, im, 2 h apart; n = 8) or 1/6PGF (single dose of 83.3 μg of cloprostenol, im; n = 10). Before treatments and every 8 h during the 48-h experimental period, blood samples were collected and CL volumes measured. Furthermore, two CL biopsies were obtained at 24 and 40 h post-treatment. The 1/6PGF treatment caused partial luteolysis, characterized by sudden decreases in plasma progesterone (P4) concentrations, luteal volume and LLC size, followed by increases (to pretreatment values) in P4 and luteal volume at 24 and 40 h post-treatment, respectively. However, at the end of the study, P4, luteal volume and LLC size were all significantly smaller than in Control cows. Temporally associated with these phenotypes, there was a lower mRNA abundance of VEGFA at 24 and 40 h, and ABCA1 at 24 h (P < 0.05). In conclusion, a sudden reduction in CL size during partial luteolysis induced by a sub-dose of PGF2α analog on day 6 of the estrous cycle was attributed to a reduction in LLC size, although these changes did not account for the entire phenomenon. In addition to its involvement in reducing CL size, decreased VEGFA mRNA abundance impaired CL development, resulting in a smaller luteal gland and lower plasma P4 concentrations compared to Control cows.
Keywords: Gene expression; Large luteal cells atrophy; Luteogenesis; Partial luteolysis